Language Issues in Morocco - Farissi, Jihane (International Journal of Linguistics, 2025)
It is well-known that Morocco is a multilingual country. The fact that a number of languages, along with their varieties, are used by the population is therefore the rule rather than the exception. So many countries exhibit the same situation and it is not an exaggeration to say that no country is monolingual in the sociolinguistic sense of this term. Indeed, even in the so- called monolingual settings in which speakers make use of only one language, these latter are observed to use different varieties of this language in accordance with various factors present in the linguistic situation like setting, topic, interlocutors, mood, etc. Language issues in many parts of the world affect a wide range of areas such as education, the public life, the media, arts, literature, politics, religion and government institutions, to name only these. In Morocco, the field of education faces a number of challenges relating to the functions of the languages in use in the country. This paper tries to investigate some of the language issues in education in Morocco through eliciting the views of a group of teachers and officials. On the basis of these views, the paper shows that the policy of arabisation has not had the expected results in education, administration and the public life in view of the fact that French and Moroccan Arabic are making substantial progress as languages of communication. The teaching of French suffers from high levels of poor proficiency on the part of the learners. The teaching of Amazighe is impeded by unsupportive official policies which do not yet recognise the rightness of teaching this language to the whole school population in the country. It is suggested that the issue of language in education in Morocco will greatly benefit from a more reasonable language policy which would guarantee equal chances of access to education for the national languages and better management of the teaching of foreign languages.